HYDRATED SUB-ARE MANTLE: A SOURCE FOR THE KLUCHEVSKOY VOLCANO, KAMCHATKA/RUSSIA - Dorendorf F.; Wiechert U.; Wörner G. (My University, 2000)
Oxygen isotope ratios of olivine and clinopyroxene phenocrysts from the Kluchevskoy volcano in Kamchatka have been studied by CO2 and ArF laser techniques. Measured δ18O values of 5.8–7.1‰ for olivine and 6.2–7.5‰ for clinopyroxene are significantly heavier than typical mantle values and cannot be explained by crustal assimilation or a contribution of oceanic sediments. Positive correlations between δ18O and fluid-mobile elements (Cs, Li, Sr, Rb, Ba, Th, U, LREE, K) and a lack of correlation with fluid-immobile elements (HFSE, HREE) suggest that 18O was introduced into the mantle source by a fluid from subducted altered oceanic basalt. This conclusion is supported by radiogenic isotopes (Sr, Nd, Pb). Mass balance excludes simple fluid-induced mantle melting. Instead, our observations are consistent with melting a mantle wedge which has been hydrated by 18O-rich fluids percolating through the mantle wedge. 18O-enriched fluids are derived from the subducted oceanic crust and the Emperor seamount chain, which is responsible for a particularly high fluid flux. This hydrated mantle wedge was subsequently involved in arc magmatism beneath Kluchevskoy by active intra-arc rifting.